Synthesis of Functional Silver Nanoparticles and Microparticles with Modifiers and Evaluation of their Anti-cancer Activity on MDA-MB-453 Breast Cancer Cell Line - Joseph, Mathew Kizhakkekara; Thangavel, Indhumathi (Free Radicals and Antioxidants)
Background: One of the most noteworthy concerns in cancer theranostics in recent decades is the outcome of unique nanoparticles for diagnosing and treating purposes. In the current study, we used unripe Garcinia cambogia fruits to create silver nanoparticles utilizing a straightforward and environmentally friendly process. Materials and Methods: When exposed to fruit extract, the hydroalcoholic silver ions were decreased and stabilized over an extended period, leading to the biogenesis of silver nanoparticles with functionalized surfaces. These organically produced silver nanoparticles' properties were examined and characterized. Results: By measuring mitochondrial membrane potential, formation of the reactive oxygen species, the viability of the cell, and activities of caspase 3 and 9 against the MDA-MB-231 (Breast Cancer Cells), we were able to demonstrate the anti-cancer effects of these nanoparticles in vitro. The findings imply that the AgNPs have cytotoxic and apoptotic characteristics. Conclusion: According to the current research, AgNPs may aid in the creation of an effective anti-cancer drug, which could result in the creation of remarkable nanomedicine for treating different types of cancer.
Keywords: Garcinia cambogia; AgNPs; Cytotoxicity; MDA-MB-231; Caspase-3; Caspase-9